Pengaruh Terapi Ayat Al-Qu’an Terhadap Ansietas Pada Mahasiswa Yang Sedang Mengerjakan Skripsi Di STIKes Ceria Buana - Junios, Junios; Sobirin, Cecep (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Anxiety is an unpleasant feeling, uneasy, worried and agitated at students who are doing skripsi. Usually there are some efforts undertaken handling as psychotherapy, psikofarmaka, psychosocial, and psikoreligius. In this study, non-pharmacological therapy is used to reduce anxiety, one of them with distraction techniques and relaxation with the therapeutic use of sound recordings al-quran which dilbacakan by a qori. Ayat al-quran hormones can reduce stress hormones, activates natural endorphins, increases the feeling of relaxation and distraction of fear, anxiety and tension, improve the system of body chemistry that lowers blood pressure and slows respiration, heart rate, pulse, and brain wave activity. The purpose of this study was to determine whether there is influence quran verses therapy for anxiety in students who are working on the thesis. This type of research is pre-experimental design with one group pretest-posttest. the study population is the entire nursing students working on theses. Samples in this study were 25 respondents taken by purposive sampling. The statistical test used was paired T-test with normal data distribution. The research result shows the distribution of data from the pretest and posttest on nursing students STIKes Ceria Buana experiencing anxiety is normal that value is -0.987 (pretest) and -0.129 (posttest). The change of pretest and posttest anxiety that have a significance level of p = 0.000 (p =